Bridging the gap in aging systems: health literacy and community health worker workforce innovation to address health-related social needs - Teresa Wagner; Sarah Murphy; Saphina Achi (Frontiers in Public Health, 2026)
Introduction Older adults experience complex health and social challenges, including chronic disease, polypharmacy, caregiving demands, social isolation, and unmet health-related social needs (HRSN). Health literacy is a cross-cutting factor influencing the ability to find, understand, communicate about, and navigate health and social services. Community health workers (CHWs) are well positioned to address these intersections, yet integrated workforce training remains limited. Methods This manuscript describes a health literacy-centered CHW and frontline workforce training model emphasizing dementia and depression screening, health literacy-informed communication, referral, and resource navigation. Developed collaboratively by the Health Literacy Lab, Community Health Worker Training Center, and Center for Older Adults at UNT Health Fort Worth, the model incorporated community-engaged curriculum development, interdisciplinary education, and cross-sector partnerships. A descriptive post-training program evaluation assessed knowledge, perceived skills, and intended application. Of 270 participants completing training, 201 completed the post-training assessment (74.4% response rate). Results Mean post-training knowledge was 84.9% (SD = 9.23). Participants demonstrated strong knowledge of dementia, depression, health literacy, culturally responsive communication, and referral practices. Participants reported confidence applying health literacy-informed communication and screening strategies, and 167 (83.1%) intended to implement strategies addressed during training. Pre-training knowledge, observed practice change, HRSN resolution, and patient outcomes were not assessed. Discussion Findings provide preliminary evidence supporting a health literacy-centered workforce development approach. The model positions health literacy as a cross-cutting competency relevant to HRSN screening, referral, and navigation and provides a framework for strengthening CHW capacity across healthcare and community settings. Longitudinal evaluation is needed to determine whether post-training knowledge and intended application translate into sustained practice changes and improved HRSN and health outcomes.